Japanese People’s Awareness of Disaster Prevention - Luo, Qihui (Journal of Social Science and Humanities, 2025)
Japan is a country where various natural disasters such as earthquakes, tsunamis, typhoons, and volcanic eruptions occur frequently. In order to cope with these potential disasters, Japanese people must possess a generally high level of disaster prevention awareness. This paper mainly discusses the formation of disaster prevention awareness among the Japanese, focusing on areas such as the establishment of disaster prevention laws, the enhancement of disaster prevention education, the preparation of daily emergency measures, disaster prevention and mitigation systems, and the high seismic resistance of buildings. It also points out the new challenges Japan faces in terms of disaster prevention.